Students’ Engagement in Narrative Writing Skills Through Digital Story Telling Platforms - Ima, Nur; Pratiwi, Dian Fera; Anggung, Sinta Dewi; Julianti , Rahmah (elstic : english language linguistics culture, 2025)
This study aims to investigate students’ engagement in improving narrative writing skills through the use of digital storytelling platforms. As writing continues to be a core component of academic success, finding innovative and engaging instructional methods has become increasingly important. Digital storytelling (DST), which combines text, visuals, audio, and multimedia elements, offers a student-centered approach that supports creativity, motivation, and deeper learning. This research employs a quantitative survey method involving 20 undergraduate students of English Education Department. The study focuses on analyzing three dimensions of engagement behavioral, emotional, and cognitive as well as students’ perceptions of how Digital story telling influences their narrative writing abilities. Data were collected through a structured questionnaire and analyzed using descriptive statistics. The results show that students demonstrated high levels of engagement across all three dimensions, with emotional engagement scoring the highest. The findings suggest that integrating digital storytelling into writing instruction can effectively foster student engagement and support the development of key writing skills. This study recommends to highlights the importance of providing technical support to maximize its impact. Future research may consider longitudinal approaches or classroom-based observations to examine long-term improvements in writing performance and digital literacy.